A new strain of Shewanella putrefaciens isolated from the dead sea of Jordan - Jacob, J.H.; Irshaid, F.I. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Halophilic bacteria flourish in environments with high salinities such as the Dead Sea of Jordan. In this current study, a new strain, assigned as DS4, was isolated from the Dead Sea of Jordan. The strain was identified based on biochemical and physiological characteristics, and it was further identified by 16S rDNA sequence analysis. DS4 was shown to be Gramnegative,oxidase-positive, non-lactose fermenting, and sulfide-producing on TSI medium. The strain was found to lack the following exoenzymes: amylase, gelatinase, and protease. Strain DS4 was able to grow at high salinity range of 3.4–4.5% NaCl and optimally at 4% NaCl. Furthermore, the 16S rRNA gene analysis revealed that the gene was 99% identical with the genes of several strains of Shewanella putrefaciens deposited in the public nucleotide database. Moreover, the antibiogram of this new strain was determined by well diffusion method. The strain was found to be sensitive to various antibiotics (at concentration of 10 mg ml-1) including cloxacillin, chloramphenicol, tetracycline, penicillin, and cyclohexamide. In view of all the above characteristics of strain DS4, it can be concluded that this isolate represents a new mild halophilic strain of Shewanella putrefaciens from the Dead Sea of Jordan.